Position statement and literature review: Youth weightlifting - Pierce, K. C.; Byrd, R. J.; Stone, M. H.
Based on a review of literature, some advices are recommended for youth weightlifting. Summary As with any sport, weightlifting competition and weightlifting training should be carried out with reasonable safety measures in place. In normal supervised environments the potential for injury is remarkably low. It is clear that the potential for injury is an issue that requires ongoing scientific study. The need to clarify anecdotal reports and conjecture regarding injury is essential. There is no doubt that competitive weightlifting can be appropriate for children who are supervised in training and competition by well-qualified professionals. Well qualified implies an understanding of the sport sciences, especially those related to developmental stages, with the ability and drive to apply this knowledge. Finally, in support of weightlifting for children, as with other sports, motivation would be minimal without some form of competition.